2013
DOI: 10.1155/2013/490857
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality, Interannual Variability, and Linear Tendency of Wind Speeds in the Northeast Brazil from 1986 to 2011

Abstract: Wind speed analyses are currently being employed in several fields, especially in wind power generation. In this study, we used wind speed data from records of Universal Fuess anemographs at an altitude of 10 m from 47 weather stations of the National Institute of Meteorology (Instituto Nacional de Meteorologia-INMET) from January 1986 to December 2011. The objective of the study was to investigate climatological aspects and wind speed trends. To this end, the following methods were used: filling of missing da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…dry and wet bulb temperature, relative humidity, wind speed and direction, cloud coverage and atmospheric pressure) from its manual network of 293 surface weather stations across Brazil. Santos and Silva (2013) describe that wind speed observations gathered from INMET follow and meet the anemometer height standard (10 m) set by the World Meteorological Organization (WMO). However, a setback of using observations from INMET is the lack of continuous periods of record for all given sites.…”
Section: In Situ Windsmentioning
confidence: 99%
See 3 more Smart Citations
“…dry and wet bulb temperature, relative humidity, wind speed and direction, cloud coverage and atmospheric pressure) from its manual network of 293 surface weather stations across Brazil. Santos and Silva (2013) describe that wind speed observations gathered from INMET follow and meet the anemometer height standard (10 m) set by the World Meteorological Organization (WMO). However, a setback of using observations from INMET is the lack of continuous periods of record for all given sites.…”
Section: In Situ Windsmentioning
confidence: 99%
“…Previous work has suggested that wind speeds are slowing across northeastern Brazil (Silva et al, 2010;Pereira et al, 2013;Santos and Silva, 2013). Yet, it has been forecasted that surface winds will increase along coastal and northeastern Brazil based on conditions implemented from IPCC emission schemes and stimulated into general climate models (Lucena et al, 2010;Pereira et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Studies for NEB include the analysis of rainfall characteristics (Rao and Hada, 1990;Rao et al, 2016), trends of (heavy) rainfall events (Oliveira et al, 2012(Oliveira et al, , 2013Priscilla et al, 2014), drought and connected vegetation dynamics (Barbosa et al, 2006(Barbosa et al, , 2015Marengo and Bernasconi, 2015), trends of maximum and minimum temperature (da Silva, 2004), or the tendency of wind speed (Alexandre and Santos e Silva, 2013). Vincent et al (2005) describe changes in the temperature extremes in South America for the period 1961-2000 that are particularly pronounced for climate indices related to minimum temperature, while those based on maximum temperature reveal no consistent changes.…”
Section: Introductionmentioning
confidence: 99%